Gerakan Literasi Sekolah di Sekolah Islam (Sebuah Analisis Implementasi GLS Di MI Muhammadiyah Gunungkidul) - Ichsan, Ahmad Shofiyuddin (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2018)
This study aims to determine the implementation of School Literacy Movement (GLS) in Islamic school, awareness of academic civitas in cultural literacy, supporting and inhibiting factors in GLS’ implementation and analysis on implementation in Islamic school. The study used is qualitative research. Subjects in this study are residents of the school and its objects are all matters related to the implementation of the School Literacy Program (GLS) in MI Muhammadiyah Pengkol Gunungkidul.The results of this study find that there is awareness with the school residents in actuating the GLS program and there are several strategies in implementing the GLS program. Supporting factors in the GLS program at this school one of them is a high awareness, good communication between school with parents and many strategies undertaken. While the inhibiting factors is the very minimal facility and hasn’t maximum support yet from the government. In the context of religion, Muslim should have a cultural literacy because it is the first teaching in the Qur'an. Challenges ahead in this case, children must have awareness to improve the quality of literacy. Nowadays, the textual reading quality of society through books is getting lower, so it is necessary to balance in understanding the phenomenon. It is also necessary to have a 'revolution' in changing the mindset of society in the literacy.